HEALTH PERCEPTION, HEALTH BELIEF MODEL-BASED SMOKING CESSATION CONSTRUCTS, AND NICOTINE DEPENDENCE AS PREDICTORS OF INTENTION TO QUIT SMOKING AMONG DEAF AND HARD-OF-HEARING YOUNG ADULTS - Deniz Şarlak (Karya Journal of Health Science, 2026)
Objective: This study aimed to examine the relationships among health perception, Health Belief Model-Based Smoking Cessation constructs, nicotine dependence, and intention to quit smoking among deaf and hard-of-hearing young adults, and to determine the predictive contribution of these variables to intention to quit smoking.Method: This cross-sectional correlational study included 680 deaf and hard-of-hearing young adults aged 18-25 years. Data were collected using the Fagerström Test for Nicotine Dependence, the Intention to Quit Smoking Scale, the Health Belief Model-Based Smoking Cessation Scale, and the Health Perception Scale. Pearson’s correlation analysis, hierarchical multiple regression, mediation analysis, moderation analysis, and structural equation modelling were performed.Results: Intention to quit smoking was significantly and positively associated with health perception and self-efficacy, and significantly and negatively associated with the HBM-SCS composite score, nicotine dependence, smoking consumption, degree of hearing loss, and perceived barriers (p